2014
DOI: 10.2147/ijn.s69572
|View full text |Cite
|
Sign up to set email alerts
|

TNYL peptide functional chitosan-g-stearate conjugate micelles for tumor specific targeting

Abstract: Nowadays, a real challenge in cancer therapy is to design drug delivery systems that can achieve high concentrations of drugs at the target site for improved therapeutic effect with reduced side effects. In this research, we designed and synthesized a homing peptide-(TNYLFSPNGPIA, TNYL) modified chitosan-g-stearate (CS) polymer micelle (named T-CS) for targeting delivery. The peptide displayed specific binding affinity to EphB4 which is a member of the Eph family of receptor tyrosine protein kinases. The amphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The TNYL peptide has also been conjugated through a C-terminal PEG linker to chitosan-g-stearate, generating an amphiphilic polymer that spontaneously forms nanosized micelles in aqueous solutions, which can be efficiently loaded with drugs or imaging agents and can be readily internalized into cells [119]. Despite the low EphB4 binding affinity of monomeric TNYL [23], the peptide could preferentially target doxorubicin-loaded nanoparticles to EphB4-positive SKOV3 ovarian cancer cells compared to non-targeted nanoparticles, leading to enhanced toxicity towards the cancer cells [119].…”
Section: Peptide Conjugates Targeting Eph Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TNYL peptide has also been conjugated through a C-terminal PEG linker to chitosan-g-stearate, generating an amphiphilic polymer that spontaneously forms nanosized micelles in aqueous solutions, which can be efficiently loaded with drugs or imaging agents and can be readily internalized into cells [119]. Despite the low EphB4 binding affinity of monomeric TNYL [23], the peptide could preferentially target doxorubicin-loaded nanoparticles to EphB4-positive SKOV3 ovarian cancer cells compared to non-targeted nanoparticles, leading to enhanced toxicity towards the cancer cells [119].…”
Section: Peptide Conjugates Targeting Eph Receptorsmentioning
confidence: 99%
“…Despite the low EphB4 binding affinity of monomeric TNYL [23], the peptide could preferentially target doxorubicin-loaded nanoparticles to EphB4-positive SKOV3 ovarian cancer cells compared to non-targeted nanoparticles, leading to enhanced toxicity towards the cancer cells [119]. In addition, in vivo imaging showed that the TNYL-targeted nanoparticles could preferentially deliver the encapsulated near-infrared dye DiR to SKOV3 mouse tumor xenografts compared to EphB4-negative A549 lung cancer xenografts.…”
Section: Peptide Conjugates Targeting Eph Receptorsmentioning
confidence: 99%
“…In this study, biofunctionalization with the ECM proteins plasma fibronectin, laminin‐111, 511, and 521 to the surface of PFC–MPs was accomplished by a coupling reaction between the carboxyl residues of proteins to the free amine residues of chitosan using EDC as a crosslinker and NHS ester as an enhancer of coupling (Figure 4a). The EDC/NHS coupling reaction is a selective method for preservation of biological activity of the protein and has previously been applied in the production of protein‐functionalized chitosan derivatives (Chen et al, 2014; Ho et al, 2005; Taylor et al, 2015). Since the pH of the reaction solution is critical for maximizing the amination reaction, we tested different pH levels keeping all other conditions the same, to determine the favored pH to maximize attachment.…”
Section: Resultsmentioning
confidence: 99%
“…New drugs are needed to replace antibiotics. Therefore, AMPs have become an important research topic due to their strong antibacterial activity (Dawgul, Maciejewska, Jaskiewicz, Karafova, & Kamysz, 2014). PMAP-37 is an AMP that was first isolated from pig myeloid cells (Tossi et al, 1995).…”
Section: Discussionmentioning
confidence: 99%